Hybridization of an unoccupied molecular orbital with an image potential state at a lead phthalocyanine/graphite interface. (14th December 2018) - Yamada, Takashi; Kawakita, Noriaki; Okui, Chiaki; Munakata, Toshiaki
Abstract: The interaction of a molecular orbital with a surface state is important to understand the spatial distribution of the wave function at the molecule/substrate interface. In this study, we focus on hybridization of an unoccupied state of lead phthalocyanine (PbPc) with the image potential state (IPS) on a graphite surface. The hybridization modifies the energy-momentum dispersions of the IPS on PbPc films as observed by angle-resolved two-photon photoemission. On the PbPc 1 monolayer film, the IPS band forms a band gap and back-folding appears at the first Brillouin zone boundary due to the periodic potential by the adsorbate lattice. The modification of the dispersion is accompanied by the intensity enhancement of the IPS. We attributed the origin of the modified dispersion and intensity enhancement to a hybridization of the IPS with a molecule-derived unoccupied level. From the photon energy-dependent measurement on multilayer films, we have found the diffuse unoccupied molecular level in the vicinity of the IPS. The tail part of the IPS wave function in the substrate is enhanced by the hybridization with the unoccupied state, and thus strengthens the transition from the occupied substrate band to the hybridized IPS.